TRADISI HANTARAN DALAM PROSESI KHITHBAH PERSPEKTIF HUKUM KELUARGA ISLAM DI DESA MENGEN KECAMATAN TAMANAN KABUPATEN BONDOWOSO - Mulyadi (ASA, 2024)
Khitbah or proposing is the first step that is actually legally permissible. Khitbah is a prelude to marriage. Khitbah or proposal is a prelude to marriage, it is recommended before there is a husband and wife bond with the aim that the time of entering marriage is based on research and knowledge and awareness of each party. The objectives of this study are (1) to describe the hantaran tradition in the Khitbah procession in Mengen Village, Tamanan Subdistrict, Bondowoso Regency, and (2) the hantaran tradition in the Khitbah procession from the perspective of Islamic Family Law in Mengen Village, Tamanan Subdistrict, Bondowoso Regency. The method used in this research is a skinative approach, the type of research is a case study. The technique of determining the informants of this study using porpusive sampling Data collection techniques in this study are The data analysis uses data collection, data reduction, data presentation, and conclusion drawing, The data validity technique used in this research is source and method tringulation. The Hantaran tradition in the Khitbah procession in Mengen Village, Tamanan Subdistrict, Bondowoso Regency involves bringing souvenirs and gifts as a symbol of seriousness in Khithbah. These gifts can include cakes, bread, toiletries, clothes, prayer tools, jewelry, etc., given to the party being proposed to or the proposing party. Not fulfilling this tradition can lead to unfavorable conversations and opinions from the local community and family. The purpose of the hantaran is to avoid controversy and negative impacts socially and culturally. It serves as a tribute to the prospective wife and her family, symbolizing the agreement and engagement bond. From the perspective of Islamic family law in the village of Mengen, this hantaran tradition is permissible and does not conflict with Sharia. It aligns with the intention of avoiding controversy and negative impacts, while honoring the prospective wife and her family and signifying the agreement and engagement between the parties.